(3efThQ aj PcQ EbGdI SYOs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf cJHJ CWGd Gddg HbGA ENhJi Cgd GdSYGOI hGdUaGA GdeJejRjf HGdCeGfI hGdSOb s
(3BNQgG (B:s
(3hjLH GdEbJUGQ HYO gPG ai GdecGJHI HYOeG JbOe ef aUd GdbSeI hGdeMGSHI hGdMeO ddg ceG gh Cgdg hUdhGJg Ydi QShdg hBdg hSde JSdjekG hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B104s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis